Modelo para determinação da pressão específica de corte na usinagem com diferentes geometrias de aresta - Perim, Carla Araújo (Universidade Federal de São Carlos, 2025)
This work presents a method for representing the effect of rounded cutting edges based on an equivalent rake angle, calculated as a weighted average of the local angles along the effective edge length. This allows the calculation of forces using mechanistic models based on the specific cutting force obtained for different rake angles. Thus, from orthogonal turning tests on brass with chamfered cemented tungsten carbide cutting inserts and varying feed rates, empirical models were fitted to calculate the specific cutting forces in the cutting and thrust directions. Subsequently, the same type of test was conducted with inserts prepared with asymmetrical edge rounding to verify the validity of the method for calculating the force components. By comparing experimental and theoretical results, relative errors between 5% and 20.5% were observed for the specific cutting force in the cutting direction, while errors between 19.4% and 31.4% were obtained in the feed direction. This variation in errors can be attributed to the instability of chip formation at smaller feed rates, which tends to increase the observed errors. In general, it can be stated that the use of the equivalent rake angle for predicting the forces acting on the cutting inserts with different edge rounding proves to be a viable alternative for process optimization.
Model for determining the specific cutting force in machining with different edge geometries
Keywords: Torneamento; Microgeometria de aresta; Modelagem de esforços de usinagem; Ângulo de saída equivalente; Turning; Cutting-edge microgeometry; Machining force modeling; Equivalent rake angle; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; 9. Indústria, Inovação e Infraestrutura